Normative spaces and legal dynamics in Africa
1 online resource (xv, 200 pages).
Keywords: "Selected case studies from thirteen African countries deliver new empirical data and grounded insights from, and into, particular normative spaces. The individual chapters explore the interrelationships between various normative orders, diverse actors, and their influences. The encounters between different normative understandings and actors open up space and multiple forums for negotiating values. The authors analyse how different doctrines, institutions, and practices are constructed, contested, negotiated, and adapted in translation processes and thereby continuously reshape Africa's multidimensional normative spaces"--